Exploring the effects of a neck strengthening program on neurocognition following purposeful soccer heading - Waring, M. K.; Smith, E. R.; Austin, G. P.; Bowman, T. G. (Journal of Athletic Training, 2019)
Context: Neck strengthening has been proposed as an important factor in concussion predisposition. However, the effect of neck strengthening programs on neurocognition after purposeful heading has not been identified. Therefore, the purpose of our study was to determine if a 6-week strengthening program increases soccer athletes' neck strength and causes changes in neurocognitive outcomes after a bout of repetitive purposeful soccer heading. Methods:Twenty collegiate soccer athletes (8 males, 12 females, age=20.15±1.35 years, height=171.67±9.01, mass=70.56±11.03) volunteered to participate. Time (pre and post) and group (experimental and control) served as the independent variables. Strength measurements in 7 directions (anterior, right anterolateral, left anterolateral, right rotation, left rotation, right posterolateral, left posterolateral) and 4 composite scores from CNS Vital Signs (CNSVS; verbal memory, visual memory, executive function, reaction time) served as the dependent variables. Each athlete completed a baseline measure of neck strength and CNSVS after heading 10 soccer balls. We used a Microfet handheld dynamometer to measure the participants' neck strength. The participants completed three trails in each direction and we calculated the average. The experimental group completed specifi c neck strengthening exercises twice a week for 6 weeks using a Shingo Imara. The neck exercises consisted of 2 sets of 4 neck movements until fatigue. The control group did not perform neck strengthening exercises. After six weeks, the athletes completed the same neck strength testing protocol and completed CNSVS again. We analyzed the data using 2x2 mixed model ANOVAs for each of the dependent variables. Results: The interaction between time and group was significant for anterior (F1,17=41.78, P=.04, n2=.22), right anterolateral (F1,17=4.80, P=.04, n2=.22), and left anterolateral (F1,17=6.48, P=.02, n2=.28) strength measurements. Post hoc tests showed strength improved pre to post in the anterior direction for both the strengthening (P<.001) and the control (P=.02) groups, but only for the strengthening group for right anterolateral (P<.001) and left anterolateral (P<.001). The interaction between time and group was not significant for right rotation (F1,17=2.12, P=.16, n2=.11, 1-ß=.28), left rotation (F1,17=3.20, P=.09, n2=.16, 1-ß=.39), right posterolateral (F1,17=2.98, P=.10, n2=.15, 1-ß=.37), or left posterolateral (F1,17=2.86, P=.10, n2=.14, 1-ß=.36) strength measurements. When determining the effects on neurocognition and symptoms, the interaction between time and session was signifi cant for visual memory (F1,17=5.16, P=.04, n2=.23). Interestingly, post hoc results revealed visual memory only improved for the control group (P=.02). The interaction between time and session was not signifi cant for verbal memory (F1,17=.01, P=.91, n2<.001, 1-ß=.05), executive function (F1,17=.71, P=.41, n2=.04, 1-ß=.13), reaction time (F1,17=1.05, P=.32, n2=.06, 1-ß=.16), or symptom severity score (F1,17=2.40, P=.14, n2=.12, 1-ß=.31). Conclusions:The strengthening program our participants completed improved anterior and anterolateral neck strength, but not rotation or posterolateral strength. Improving strength in these locations did not alter neurocognition following repetitive soccer heading.